Pulses Production in Lalitpur District of Bundelkhand: Constraints and Opportunities - Pandey, Nitin; Dikshit, Archana; Tiwari, Dinesh; Yadav, NK; Somvanshi, SPS (Indian Journal of Extension Education, 2021)
Per capita net availability of pulses in the country declined sharply over the years due to stagnation of productivity as well as decline in area. For present study, fifteen villages of three blocks and from each village 12 farmers were selected randomly making a total of 180 farmers from Lalitpur district of Bundelkhand region to find out the constraints and opportunities in pulse production. It was revealed that stray animal & blue bull, middle man and lack of education were socio-personal constraints. Among infrastructural constraints lack of irrigation facility, non availability of quality seed were major. Other constraints included high infestation of pest and diseases (wilt, root rot and pod borer), non availability of inputs at proper time (quality seed, bio-pesticide and herbicides etc.), low market price, lack of technical guidance as perceived by the pulse farmers.